2008
DOI: 10.4103/0019-509x.44666
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum squamous cell carcinoma antigen as a novel biomarker for diagnosis of hepatocellular carcinoma in Egyptian patients

Abstract: BACKGROUND: Hepatocellular carcinoma (HCC) is the fi fth most common malignancy in the world. In Egypt, HCC was reported to account for about 4.7% of chronic liver disease (CLD) patients. Squamous cell carcinoma antigen (SCCA) has been reported to be strongly expressed in HCC tissue hampering its extensive use in clinical practice. AIM: To evaluate the clinical usefulness of serum SCCA levels as a serological marker for early detection of HCC among high-risk patients compared to AFP. MATERIALS AND METHODS: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…1) [713]. Two articles described Golgi protein 73 (GP73) as a HCC biomarker [7, 8], two described interleukin-6 (IL-6) [9, 10], and three described squamous cell carcinoma antigen (SCCA) [1113]. All identified studies provided level 2b evidence on the Oxford Level of Evidence scale and included a control group with ≥10 cirrhotic patients (hepatitis B and/or hepatitis C and/or alcohol abusers), ≥10 patients with a HCC, and ≥10 confirmed healthy persons [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) [713]. Two articles described Golgi protein 73 (GP73) as a HCC biomarker [7, 8], two described interleukin-6 (IL-6) [9, 10], and three described squamous cell carcinoma antigen (SCCA) [1113]. All identified studies provided level 2b evidence on the Oxford Level of Evidence scale and included a control group with ≥10 cirrhotic patients (hepatitis B and/or hepatitis C and/or alcohol abusers), ≥10 patients with a HCC, and ≥10 confirmed healthy persons [5].…”
Section: Resultsmentioning
confidence: 99%
“…SCCA, a component of the high molecular weight serine protease inhibitors named serpins, is physiologically expressed in the squamous epithelia [1113]. Increased levels have been detected in several epithelial cancers such as those of the head, neck, cervix, and lung [1113].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Squamous cell carcinoma antigen (SCCA) which represents a family of serine proteases of high molecular weight, also known as serpins. Hussein et al (54), reported the potential value of SCCA in the diagnosis of HCC. The Sensitivity and specificity for SCCA in HCC diagnosis are 77.6% and 84%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-fetoprotein (AFP) is the only biomarker used for HCC diagnosis, however, its use in the early detection of HCC is limited, especially because about one-third parts of patients with HCC have normal levels of serum AFP [66]. Serum AFP is a marker that has low sensitivity and high specificity [8, 24, 67].…”
Section: Novel Serum Biomarker Candidate For the Enhanced Detection Omentioning
confidence: 99%